CLINICO BIOCHEMICAL FEATURES OF ACUTE VIRAL HEPATITIS A PATIENTS IN RELATION TO DEMOGRAPHIC FACTORS IN HILLY AREAS OF GARHWAL REGION OF UTTARAKHAND (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To observe prevalence of hepatitis A between spring water and tap water consumers among rural and urban population. Methodology: This descriptive cross-sectional study was conducted over six months in selected healthcare facilities and communities across the Garhwal region. A total of 104 patients diagnosed with Acute Viral Hepatitis A were included after laboratory confirmation by IgM anti-HAV antibody testing. Data on demographic characteristics, clinical symptoms, and biochemical parameters were collected using structured questionnaires and laboratory records. Results: Among the 104 patients, 58 (55.8%) were from rural areas and 46 (44.2%) from urban areas. The mean age was 29.6 ± 10.8 years, and males (60.6%) were more affected than females (39.4%). The majority of patients were young adults aged 18–35 years, and most rural cases were farmers or laborers. Common clinical features included jaundice (94.2%), malaise (88.5%), nausea/vomiting (75.0%), and abdominal discomfort (61.5%). Biochemically, mean SGOT and SGPT levels were 1478.5 ± 955.6 U/L and 2010.3 ± 840.2 U/L, respectively, while mean total bilirubin was 3.8 ± 1.4 mg/dL. Hepatic encephalopathy occurred in 7 (6.7%) patients, and no mortality was observed. Water testing revealed bacterial contamination in 68.9% of rural samples compared to 26.1% in urban areas (p < 0.01), indicating unsafe drinking water as a major contributing factor. Conclusion: The incidence of Acute Viral Hepatitis A was higher among rural residents of the Garhwal region, predominantly affecting young males exposed to contaminated spring water. The majority of cases were mild and self-limiting, but poor sanitation and unsafe water sources remain major risk factors.